A search for reverse transcriptase-coding sequences reveals new non-LTR retrotransposons in the genome of Drosophila melanogaster. - Berezikov, E.; Bucheton, A.; Busseau, I. (Genome Biology, 2000)
Non-long terminal repeat (non-LTR) retrotransposons are eukaryotic mobile genetic elements that transpose by reverse transcription of an RNA intermediate. We have performed a systematic search for sequences matching the characteristic reverse transcriptase domain of non-LTR retrotransposons in the sequenced regions of the Drosophila melanogaster genome.In addition to previously characterized BS, Doc, F, G, I and Jockey elements, we have identified new non-LTR retrotransposons: Waldo, You and JuanDm. Waldo elements are related to mosquito RTI elements. You to the Drosophila I factor, and JuanDm to mosquito Juan-A and Juan-C. Interestingly, all JuanDm elements are highly homogeneous in sequence, suggesting that they are recent components of the Drosophila genome.The genome of D. melanogaster contains at least ten families of non-site-specific non-LTR retrotransposons representing three distinct clades. Many of these families contain potentially active members. Fine evolutionary analyses must await the more accurate sequences that are expected in the next future.